Antiacne and antiblotch activities of a formulated combination of Aloe barbadensis leaf powder, Garcinia mangostana peel extract, and Camellia sinensis leaf extract - Waranuch N; Phimnuan P; Yakaew S; Nakyai W; Grandmottet F; Onlom C; Srivilai J; Viyoch J (Dove Medical Press, 2019)
Neti Waranuch,1,2 Preeyawass Phimnuan,2 Swanya Yakaew,2 Wongnapa Nakyai,3 Francois Grandmottet,4 Churanya Onlom,5 Jukkarin Srivilai,6 Jarupa Viyoch1,21Cosmetics and Natural Products Research Center, Faculty of Pharmaceutical Sciences Naresuan University, Phitsanulok 65000, Thailand; 2Department of Pharmaceutical Technology, Faculty of Pharmaceutical Sciences and Center of Excellence for Innovation in Chemistry, Naresuan University, Phitsanulok 65000, Thailand; 3Department of Chemistry, Faculty of Science, Ramkhamhaeng University, Bangkok 10240, Thailand; 4Department of Biochemistry, Faculty of Medical Science, Naresuan University, Phitsanulok 65000, Thailand; 5Aga Siam, Phitsanulok, 65000, Thailand; 6Department of Cosmetic Science, School of Pharmaceutical Sciences, University of Phayao, Phayao 56000, ThailandObjective: We compared the efficacy of an antiacne hydrogel formulated with a combination of Aloe barbadensis leaf extract, Garcinia mangostana peel extract, and Camellia sinensis leaf extract (AGC) at a ratio of 50:25:1 with a marketed 1% clindamycin gel (CG) formulation on antiacne and antiblotch activities.Methods: A single-center, parallel-arm, randomized controlled trial was performed from November 2017 to April 2018. Sixty subjects with mild–moderate acne severity according to the the American Academy of Dermatology were enrolled for the study. Outcome end points were total acne lesions (TALs) and acne-severity index (ASI) by counting the inflamed lesions and comedones and skin colors using erythema and melanin values.Results: For TALss, a decrease (P<0.0001) in the number of total inflamed lesions from baseline was evidenced in AGC group, but not in the CG group. Higher reduction in mean ASI in the AGC group was seen than in the CG group. However, there was no statistically significant difference regarding reduction in ASI between the AGC and CG groups. For erythema, a remarked reduction in skin redness from baseline was clearly seen at day 3 (P<0.05) in the AGC group. No significant decrease in erythema values from baseline was seen in the CG group. A significant decrease (P=0.037) in mean melanin value from baseline was seen in the AGC group after 14 days of twice-daily use, but not in the CG group. Both products were well tolerated, with no reports of severe adverse events.Conclusion: An anti-acne hydrogel containing a combination of mangosteen rinds, aloe vera gel, and green tea–leaf extracts was superior to 1% clindamycin gel in antiacne and antiblotch activities when measured by TALs and erythema and melanin values.Keywords: herbal extracts, acne, inflamed lesions, mangosteen rinds, aloe vera gel, green tea leaf